Food commercials do not affect energy intake in a laboratory meal but do alter brain responses to visual food cues in children. (1st January 2019) - Masterson, Travis D.; Bermudez, Maria A.; Austen, Marielle; Lundquist, Ella; Pearce, Alaina L.; Bruce, Amanda S.; Keller, Kathleen L.
Abstract: Food commercials promote snack intake and alter food decision-making, yet the influence of exposure to food commercials on subsequent neural processing of food cues and intake at a meal is unclear. This study tested whether exposing children to food or toy commercials altered subsequent brain response to high- and low-energy dense food cues and influenced laboratory intake at a multi-item, ad libitum meal. Forty-one 7-9-year-old children (25 healthy weight; 16 with overweight/obesity) completed five visits as part of a within-subjects design where they consumed multi-item test-meals under three conditions: no exposure, food commercial exposure, and toy commercial exposure. On the fourth and fifth visits, functional magnetic resonance imaging (fMRI) was performed while children viewed low- and high-energy dense food images following exposure to either food or toy commercials. Linear mixed models tested for differences in meal energy intake by commercial condition. A whole-brain analysis was conducted to compare differences in response by commercial condition and child weight status. Meal intake did not differ by commercial condition ( p = 0.40). Relative to toy commercials, food commercials reduced brain response to high-energy food stimuli in cognitive control regions, including bilateral superior temporal gyri, middle temporal gyrus, and inferior frontal gyrus. Commercial condition * weight status interactions were observed in orbitofrontal cortex, fusiform gyrus, and supramarginal gyrus. Children with overweight/obesity showed increased response in these regions to high-energy stimuli following food commercials. Food commercial exposure affected children's subsequent processing of food cues by reducing engagement of the prefrontal cortex, a region implicated in cognitive control. Even though food commercial exposure did not increase intake at a meal, the effect of reduced prefrontal cortical engagement on a broader range of consumption patterns warrants investigation.